Effects of a Temperature Distribution on a Dental Crown System/Analysis, Design and Control of a Hovercraft Model - Snider, Katherine (My University, 2007)
Dentral Crown: A dental crown system is a type of extracoronal restoration, or a restoration that exists around a remaining tooth structure. It is used in situations where there is not enough remaining solid tooth structure after decay or when a tooth has fractured and is missing important structural reinforcements. It typically consists of four layers, including the original tooth core, a layer of cement, a crown layer to provide the structural support, and a veneer layer that gives the look of a real tooth. All of these layers were created and assembled in order to accurately represent a crown system for the project. The goal of this project is to determine the effects of a temperature change on the maximum principle stress for the crown layer of the system. This helps determine how long the crown can be used before it will break. Temperature and stress analyses will be done for four different material combinations in order to see what effect these have on the system as well as what materials are better to use for a crown system. Hovercraft: A hovercraft is a special type of vehicle that moves on a cushion of air. The lifting motion is controlled by a fan or fans so that an air gap can be formed beneath the vehicle. Such separation between the bottom of the hovercraft and the ground provides a motion platform, on which the friction force between the hovercraft and the ground reduces to a very small amount. Since a hovercraft does not have wheels, the forward motion is created through propulsion, which is generated by the use of a fan or set of fans located on the back end of the hovercraft. These propulsion fans send the air backward to produce a thrust force, which moves the hovercraft forward. The goal of this project is to analyze, create, and control a working hovercraft model. Initially, flow analysis will be performed on a hovercraft model created in SolidWorks. After a design has been found that provides the necessary lift force, the model will be constructed using materials provided by the University of Maryland. Once the model is assembled and working, programming will be done in order to control the motion of the hovercraft. This will be done using an NXT control box. The ultimate goal is to have the model follow a specified path by using feedback from light sensors to control the movement.
Keywords: hovercraft; control; flow analysis; NTX control box; light sensors; dental crown; temperature change; stress analysis